(untitled) (Research, Society and Development, 2022)
Several snake species are under some degree of extinction threat, generated mainly by human poaching, based on mystical-religious fear, and habitat loss. However, it is possible to avoid extinction processes by using reproductive biotechnologies with the purpose of producing offsprings in order to reinsert these species in their natural environment. In this regard, the objective of this study is to conduct a scientometric survey about assisted reproduction in snakes in the last 50 years, without a geographical cut-off. Web of Science, Scopus, Science Direct, Pub Med, Scielo and Google Academic databases were used with the term: snake sperm and snake artificial insemination. In total, 22 papers related to the theme were selected, 21 of them published in 16 different journals, and one book chapter. The Google Scholar database presented 100% of the selected materials, being the most complete platform among those evaluated. Regarding the authorship of these studies, 19 research institutions from five countries actively participated in their production. An average productivity of 0.53 studies per year was found, starting from the first publication in 1980. The species Elaphe gutatta was the most commonly used model, participating in 4 (19.04%) surveys. We conclude that reproduction biotechnologies applied to snakes has a good adherence in scientific journals, and has a high potential to be used as a conservationist tool in the taxon, however, new studies, with more solid methodologies, are necessary to validate this technological resource, especially in relation to artificial insemination, which is the major target of this field.